Video Game Engagement: A Passkey to the Intentions of Continue Playing, Purchasing Virtual Items, and Player Recruitment (3Ps) - null Laurence; Asep Hermawan; Innocentius Bernarto; Ferdi Antonio (International Journal of Computer Games Technology)
People of all ages enjoy playing games, making online gaming a part of the modern lifestyle. Online games as digital products can reach gamers without being hindered by various limitations such as time and location. With a large selection of freemium and premium games in the virtual marketplace, gamers have the opportunity to switch between various games from different genres and make purchases of virtual goods. Therefore, the challenge that developers have to overcome is whether gamers will have the intention to play, pay, and recruit players (3Ps). To manage future behavior intentions, game developers need to ensure that gamers and the games they play have a solid engagement. Data collection comes from the results of distributing questionnaires to Twitter users with the self-reporting method. The amount of data processed was 370 respondents. The model was assessed using the partial least square of structural equation modeling. The results of this study show that video game engagement plays a crucial role as a mediator between gamer experience and the intention to continue playing, purchase game items, and recruit new players. Enjoyment is the strongest predictor of gamer experience, followed by arousal, social interaction, escapism, and challenge.